Major Factor of Disruption in IT Project in Public Companies - Nur Amira Syafiqah Rosli,; Nur Syazwani Suhaimi,; Nur Izzaty Hawa Zanal,; Nurul Nasyitah Mohd Rizam,; Nurul Aisyah Samijan,; Nur Athirah Batrisyia Hamizul,; Nurul Najwa Mardiustari,; Nurul Fatihah Shahzan,; Nur Liyana Sulaiman, (Applied Information Technology And Computer Science, 2023)
Since 1997, a North African government has invested significantly in modernising a key public sector company as part of broader public sector upgrades. This company launched numerous IT-based projects to digitise paper-based services, aiming to expand services and improve quality. However, these numerous IT projects have led to issues such as delays, cancellations, over budgets, and dissatisfaction among staff and clients. This study, involving 30 experienced project developers and engineers in the company's IT department, identifies key causes of project disruptions. The major disruption factors revealed in the study include the absence of a business plan, inadequate documentation, unclear quality standards, ineffective risk management, and human resources management issues.  In the end, the implications of these findings for the project manager to improve IT project management standards in the public sector are addressed.